Letter from the Editor - Edmundo Mora (Asociación Colombiana de Profesores de Ingles, 2016)
Once again the Editorial Committee has been concerned with the next ASOCOPI National Congress. Keeping this in mind, the Committee has prepared this issue to give its readers the opportunity of enjoying its contents while attedning the Congress.